Impact of COVID-19 lockdown on physical activity behaviours of older adults who participated in a community-based exercise program prior to the lockdown - Kaoru Nosaka; Caitlin Fox-Harding; Kazunori Nosaka (Public Library of Science (PLoS), 2022)
This study investigated the impact of the 2020 COVID-19 lockdown on community-dwelling older adults attending a community-based exercise program to seek strategies to keep them active during self-isolated situations. A two-phase mixed methods approach included a survey followed by in-person focus groups. Forty-eight participants, with 32 starting a community-based exercise program before the lockdown and 16 joining the program after the lockdown, completed a questionnaire survey about physical activities before and during the lockdown. This was followed by three focus groups (26 participants in total) to identify factors influencing physical activity behaviours found in the survey. The survey found that the COVID-19 lockdown had varied impact on exercise adherence of the older adults: 43% of the participants exercised less during the lockdown than pre-lockdown, but 26% exercised more. Interestingly, among the participants approximately 80% still achieved the recommended physical activity level by the WHO during the lockdown. The focus groups revealed that exercise behaviours before the lockdown directly affected the behaviours during the lockdown. Participants' recognition of the support from trustworthy people also influenced their motivation to perform exercises in an isolated environment. Remote exercise programs, such as digital and printed exercise materials, were found beneficial for the participants only when they came from the people the older adults trusted through their previous experience (i.e., the program). A sense of belonging to the exercise group was also essential for the participants to achieve self-managed exercise. It was concluded that older adults need connections to an exercise group and a trustworthy exercise instructor who could continuously support them to be physically active in isolated situations such as lockdowns, in addition to exercise knowledge and a better understanding of the benefits of exercise.